Pelaksanaan Akad Murabahah Dalam Perbankan Syariah (Studi Kasus Putusan Pengadilan Agama Jakarta Pusat Nomor 1203/PDT.G/2018/PA.JP): Implementation of Murabahah Agreements in Sharia Banking (Study of Central Jakarta Religious Court Decision Number 1203/PDT.G/2018/PA.JP) - Febrizka Taufani; Siti Nurbaiti (Faculty of Law, Universitas Trisakti, 2024)
Activities carried out by Sharia Banking must be based on sharia principles. Sharia banking is regulated in Law Number 21 of 2008 concerning Sharia Banking. Likewise, the products issued must be based on sharia principles, such as the Murabahah Agreement product. “The decision of the Central Jakarta Religious Court Number 1203/Pdt.G/2018/PA.JP” submitted an application for the Murabahah Agreement. The formulation of the problem in this research is whether the Court's decision Religion of Central Jakarta Number 1203/Pdt.G/2018/PA.JP regarding whether the Murabahah Agreement is in accordance with Law Number 21 of 2008 concerning Sharia Banking? This research uses a normative juridical research type which is descriptive and analyzed qualitatively by drawing conclusions logically deductively. The results of the discussion indicate that the dispute resolution is not yet in accordance with the regulations, and the conclusion is that the implementation of the Murabahah contract does not comply with the provisions of Law Number 21 of 2008. Meanwhile, based on Article 55 of Law Number 21 of 2008, there is authority to examine and adjudicate the implementation of the Murabahah contract.